1998
DOI: 10.1021/ma971206w
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Phase Equilibria in Polydisperse Polymer/Liquid Crystal Blends

Abstract: A thermodynamic analysis of phase equilibria in polydisperse polymer−liquid crystal blends is presented. Three different systems were analyzed:  (a) a high molar mass polydisperse polystyrene (PS) blended with 4-cyano-4‘-n-heptylbiphenyl (7CB), (b) a low molar mass polydisperse PS blended with 7CB, and (c) an epoxy-based thermosetting polymer blended with a mixture of small mesogenic molecules usually called E7. In the latter case the analysis was performed in both pregel and postgel stages. Macroscopic phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…[80,88±94] Important parameters include initial monomer/polymer and liquid crystal solution concentrations, [79,95±97] rate of polymerization, [79,82,95,98] polymer molecular weight, [90] temperature, [79,98,99] and even the presence of gravitational fields. [88,100] Therefore, films with spatially varying properties are often obtained since a number of these parameters may vary spatially during PDLC production.…”
Section: Phase Separation Methodsmentioning
confidence: 99%
“…[80,88±94] Important parameters include initial monomer/polymer and liquid crystal solution concentrations, [79,95±97] rate of polymerization, [79,82,95,98] polymer molecular weight, [90] temperature, [79,98,99] and even the presence of gravitational fields. [88,100] Therefore, films with spatially varying properties are often obtained since a number of these parameters may vary spatially during PDLC production.…”
Section: Phase Separation Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Most of these blends exhibit a liquid-liquid (L-L) immiscibility region in their phase diagrams that precedes the formation of a nematic phase during the cooling step. Therefore, the generated morphologies are determined by the mechanism of the previous L-L phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…Aims of this study were: a) to build-up the phase diagram of a polydisperse PS-EBBA blend in the whole composition range, including the stability regions of nematic and crystalline phases (previous reported phase diagrams were restricted to the region of low PS concentrations [1] or did not distinguish between nematic and crystalline phases [3] ); b) to assess the suitability of the Flory-Huggins-Maier-Saupe (FHMS) model, extended to take polydispersity of the thermoplastic polymer into account [12] to fit the experimental isotropic-nematic curve in a large composition range (the extended model was previously applied to blends exhibiting an L-L immiscibility region in the phase diagram); [12] c) to analyze the influence of the cooling rate on the distribution of the particle sizes.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the difference of compositions between E7 (N) and S A LC and in spite of the fact that polymerization induced phase separation can change the composition of the initial LC mixture 22) , the evolution of the separated mesomorphic phase is consistent with the previously modeled results on system A (i. e. in the presence of E7), which showed that a separation between the epoxide-amine i-mers and a nematic phase gives a nearly pure nematic phase. It was shown by modeling that growing i-mers are excluded progressively from the mesophase 19,20) . The diffraction intensity (integrated and expressed in arbitrary unit) as a function of time is represented in Fig.…”
Section: Analysis Of Phase Separation By X-ray Diffractionmentioning
confidence: 99%
“…decomposition can be found for isotropic isomolecular thermoplastic polymer blends 16) or examples of experimental studies by SAXS for reactive isotropic thermoset/ elastomer blends 17,18) . When initially miscible monomers/LC isotropic solutions polymerize isothermally, phase separation is induced by the evolution of free energy of mixing, DG m , with the extent of reaction, x. DG m depends upon enthalpic, entropic, anisotropic (nematic or smectic) and elastic energy terms after gelation [19][20][21] . The conversion at phase separation, usually named cloud point conversion x CP , depends on the dominance of each of these terms as well as on the concentration and temperature chosen 14,19) ; it also governs the subsequent development of morphology.…”
Section: Introductionmentioning
confidence: 99%